2006
DOI: 10.1007/s10397-006-0174-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic entry techniques: a protocol for daily gynaecological practice in The Netherlands

Abstract: This Dutch model protocol aims to formulate recommendations on insertion of laparoscopic instruments in order to reduce entry-related complications. It was written on behalf of the Dutch Society of Gynaecological Endoscopy and Minimal Invasive Surgery and serves as guidance to safe entry in laparoscopy for the Dutch gynaecologist in daily practice. It was translated and made suitable for publication in English. Despite the variety of methods described for creating pneumoperitoneum, no one single method can cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…For laparoscopic surgery different approaches have been created nowadays [10,11]. A few international investigations have proposed principal of safe laparoscopic entry [12][13][14][15][16]. Open laparoscopy named as Hasson and close, direct entry laparoscopy is used in general surgery [17].…”
Section: Introductionmentioning
confidence: 99%
“…For laparoscopic surgery different approaches have been created nowadays [10,11]. A few international investigations have proposed principal of safe laparoscopic entry [12][13][14][15][16]. Open laparoscopy named as Hasson and close, direct entry laparoscopy is used in general surgery [17].…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to minimize the risks of laparoscopy and unify clinical practice, a number of international bodies (International Middlesbrough Consensus [96], RCOG [draft version only] [97], SOGC [78], RANZ-COG [98], EAES [99], Society of American Gastrointestinal Endoscopic Surgeons [SAGES] [100], the French Society of Endoscopic Gynecology [101], the Netherlands [102] and individual experts [103][104][105]) have recommended specific ''safe laparoscopic entry'' principles. In fact, several small studies [106][107][108] have shown that adoption of a recommended technique [78,96] can reduce the incidence of laparoscopic entry-related complications.…”
mentioning
confidence: 99%